2012
DOI: 10.1038/oby.2011.343
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Body Fat Evaluation, Body Adiposity Index, Is Useful in Women With Familial Partial Lipodystrophy

Abstract: BMI is a widely used method to evaluate adiposity. However, it has several limitations, particularly an inability to differentiate lean from fat mass. A new method, body adiposity index (BAI), has been recently proposed as a new measurement capable to determine fat excess better than BMI. The aim of this study was to investigate BAI as a mean to evaluate adiposity in a group of women with familial partial lipodystrophy (FPLD) and compare it with BMI. Thirteen women with FLPD Dunnigan type (FPLD2) and 13 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
1
27
1
2
Order By: Relevance
“…ROC analysis revealed superior discrimination of BMI, compared to BAI, for obesity based on BF%. These findings contrast with previous results demonstrating that BAI showed stronger correlations with total fat and fat mass 12,13,15. Our results were comparable to other recent studies which showed that BMI is more strongly associated with adiposity and metabolic risk factors than is BAI 16,17,18,19,20.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…ROC analysis revealed superior discrimination of BMI, compared to BAI, for obesity based on BF%. These findings contrast with previous results demonstrating that BAI showed stronger correlations with total fat and fat mass 12,13,15. Our results were comparable to other recent studies which showed that BMI is more strongly associated with adiposity and metabolic risk factors than is BAI 16,17,18,19,20.…”
Section: Discussioncontrasting
confidence: 73%
“…Another study demonstrated that BAI could also be used to determine the fat content in patients with adipose tissue scarcity, such as individuals with familial partial lipodystrophy. The percentage of total adipose tissue measured by DXA was strongly correlated with BAI and was more strongly correlated with leptin levels than BMI 13. However, only one study has attempted to validate the BAI on an Asian population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A validade do IAC está bem documentada na literatura 13, [16][17][18][19][20][21][22][23][24][25][26][27]37 , porém estudos da prevalência do excesso de adiposidade corporal utilizando o IAC e fatores associados não foram identificados, até o presente momento. Este é o primeiro estudo, de que se tem conhecimento, que se concentrou em identificar a prevalência de adiposidade corporal em adultos pelo IAC e associá-lo a fatores sociodemográficos, comportamentais, de morbidades autorreferidas e de percepção.…”
Section: Discussionunclassified
“…Além disso, Carpio Rivera et al 24 verificaram a capacidade do IAC em predizer o percentual de gordura corporal em estudantes da Costa Rica. Com a população brasileira, foram conduzidos estudos para estimar o risco para o diabetes mellitus tipo 2 20 , avaliar a gordura corporal em adultos de ambos os sexos com doença renal crônica 25 e em adultos com obesidade severa 26 ; para verificar a sua validade em mulheres brasileiras na meia-idade 27 e com mulheres com lipodistrofia 17 . No entanto, não foram encontrados estudos que identificaram a prevalência de excesso de adiposidade corporal em adultos e seus fatores associados utilizando o IAC.…”
Section: Introductionunclassified